1982
DOI: 10.1111/j.1365-2621.1982.tb07618.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on the Decomposition of Pacific Coast Shrimp (Pandalus jordani)

Abstract: Shrimp (Pandalui jordani) were allowed to decompose at five temperatu!es (0, 5.6, 11.1, 16.7 and 22.2'C). Mean aerobic plate counts on the shrimp as received at the laboratory were 1.6 x 106/g. The most rapid growth was obtained at the higher temperatures but the highest maximum population was obtained at 0°C. A total of 638 bacteria were isolated and tested for identification. The heterogenous population at day 0 was composed of 38% Gram positives. The population changed becoming predominantly Gram negative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 12 publications
3
17
0
1
Order By: Relevance
“…Unlike other crustaceans (e.g., crabs and lobsters), which can be kept alive until processing, shrimps die soon after being caught, and they are often contaminated with bacteria from their endogenous microflora, as well as from the mud trawled up with them (1). Therefore, the storage temperature is crucial 20). For instance, as reported by Mendes et al (21), sensory analysis of fresh samples showed that raw chilled shrimps reached the limit of acceptability (50% rejection) after 4 days in ice, whereas 100% of the samples stored at room temperature (22°C) were rejected after 24 h.…”
Section: Discussionmentioning
confidence: 89%
“…Unlike other crustaceans (e.g., crabs and lobsters), which can be kept alive until processing, shrimps die soon after being caught, and they are often contaminated with bacteria from their endogenous microflora, as well as from the mud trawled up with them (1). Therefore, the storage temperature is crucial 20). For instance, as reported by Mendes et al (21), sensory analysis of fresh samples showed that raw chilled shrimps reached the limit of acceptability (50% rejection) after 4 days in ice, whereas 100% of the samples stored at room temperature (22°C) were rejected after 24 h.…”
Section: Discussionmentioning
confidence: 89%
“…The authors hypothesized that although in low number, the microorganisms had more time (sensory rejection time at 0 C longer than sensory rejection times at other storage temperatures) to produce metabolites that were accumulated over the storage period. The increase in TVBN levels at 0 C while the TVC counts were relatively low could also be explained by the fact that in addition to microbial spoilage, shrimp tissue enzymes also contribute to the production of volatile bases (Matches, 1982;Mendes et al, 2002;LopezCaballaro et al, 2007).…”
Section: T a ( C)mentioning
confidence: 93%
“…However, the captured shrimps are susceptible to decompose because of the existence of spoilage bacteria such as Shewanella putrefaciens and Pseudomonas spp. (Chinivasagam, Bremner, Thrower, & Nottingham, 1996;Matches, 1982). The activities of polyphenoloxidase (PPO) in hemolymph (Sö derhä ll, Cerenius, & Johansson, 1994) and cuticle (Ferrer et al, 1989) lead to melanosis (black spots formation), which spoils the organoleptic quality of shrimp.…”
Section: Introductionmentioning
confidence: 98%